Respuestas adaptativas, derecho a la salud y el límite del criterio de satisfacción: una reflexión y puesta en evidencia desde el sistema de salud peruano - Cornejo Amoretti, Leandro (2024)
Some utilitarian readings present in bioethics emphasize the importance of satisfying people’s preferences as a significant criterion of justice. One of its recurring applications in the healthcare sector is through measuring the satisfaction of healthcare service users. However, little has been discussed in the healthcare and bioethics field regarding objections that this criterion has faced from the philosophy of law and political philosophy. One of these, known as the problem of adaptive responses, asserts that individuals, whether consciously or not, adjust their satisfaction based on what they can attain. Therefore, a cautious view of this criterion is recommended, especially when measuring the satisfaction of individuals facing deprivations. Greater caution should be exercised when it is applied to services that guarantee fundamental rights, such as the right to health. This article aims to discuss this issue and highlight its presence in the healthcare services of Peru. Specifically, after tentatively and briefly conceptualizing what an inappropriately adaptive response would be, this problem will be analyzed and evaluated based on certain components of the National Survey of User Satisfaction of Universal Health Assurance (Ensusalud) of 2014, 2015 and 2016, which are the only three surveys of this kind conducted in Peru to date and on a national scale. In more detail, the aim is to determine whether significant differences in satisfaction with their health insurance exist among users based on their income levels, considering the same degree of impact on their right to health. The processing and analysis of the database lead to the conclusion that these differences do indeed exist. Faced with a infringement on this right (for example, not receiving any medication at the pharmacy, taking more than ninety minutes to reach the facility, etc.), severe economically deprived users express higher levels of satisfaction with their insurance compared to users without economic deprivations. This provides indications to suspect that, in relation to the first group of users, there might indeed be a case of adaptive responses.